Comparative Analysis of Crop Advisory Centres in Warangal District of Andhra Pradesh - Chirag Jain; Aldas Janaiah; Seema (Journal of Agricultural Extension Management, 2025)
A study was conducted to carry out a comparative analysis of Rallis Crop Advisory Centre (RCAC), District Agricultural Advisory and Transfer of Technology Centre (DAATTC) and Mahindra Samriddhi (MS) in Warangal district of Andhra Pradesh. The data were collected from 135 farmers among which 90 were users and 45 were non-user farmers. The comparison of the performance of the Crop Advisory Centres (CAC’.s) in technology advisory and delivery services was done by effectiveness index and rating index method. This paper also discusses the comparative impact of CAC’s on farmers ’ income during the rice season of 2010-2011. The study revealed that the performance of extension services rendered by the RCAC was found to be better than DAATTC and MS. Even the overall rating index of RCAC was better than DAATTC and MS. The findings also revealed that the overall impact of DAATTC services was more than RCAC and MS, on farmers ’ income.